Modulation of intestinal microbiota as a mechanism of cardiovascular pathology formation in patients with ulcerative colitis - Bikbavova, G.R.; Livzan, M.A.; Blokh, A.I.; Lisyutenko, N.S.; Zaporenko, M.Yu; Romanyuk, A.E.; Mashnin, M.Yu (РМЖ: Медицинское обозрение, 2025)
Aim: to evaluate contribution of intestinal microbiota (IM) in patients with ulcerative colitis (UC) to formation of a cardiovascular risk. Materials and Methods: IM composition was studied in an open cross-sectional study in patients with UC (n=40) (6 of which had arterial hypertension [AH]), patients with cardiovascular diseases (CVD) (n=20) and healthy individuals (n=20). α-diversity (Chao 1 index and Shannon index) and β-diversity were studied, average length of sequenced genomes was evaluated, and representation at levels of species, genus, family, and type was determined by nanopore sequencing. Results: a significant decrease in α-diversity was detected in patients with UC and AH. In non-UC patients with ischemic heart disease, a microbial profile is structurally more similar to that of healthy individuals (β-diversity). However, there is a decrease in representation of Verrucomicrobiota (including Akkermansia muciniphila), as well as anaerobic Bacillota phylum (Mediterraneibacter faecis и Eubacterium coprostanoligenes). Typically, decreases in representatives of Bacillota phylum (Anaerotruncus rubinifantis and Coprococcus eutactus) involved in production of short-chain fatty acids, as well as in proportion of underinvestigated Maliibacterium massiliense and Papillibacter cinnamivorans are reported in UC patients. Stability of average length of microbiome genomes in the study subjects suggests a potential for dysbiosis management through balanced nutrition. Conclusion: the results expand our understanding of a role of the microbiota in pathogenesis of UC and CVD, and they emphasize importance to recover butyrate-producing bacteria and to use personalized approaches to comorbidity management. KEYWORDS: ulcerative colitis, cardiovascular diseases, intestinal microbiota, microbiota, α-diversity, β-diversity, sequencing. FOR CITATION: Bikbavova G.R., Livzan M.A., Blokh A.I., Lisyutenko N.S., Zaporenko M.Yu., Romanyuk A.E., Mashnin M.Yu. Modulation of intestinal microbiota as a mechanism of cardiovascular pathology formation in patients with ulcerative colitis. Russian Medical Inquiry. 2025;9(5):266–274 (in Russ.). DOI: 10.32364/2587-6821-2025-9-5-2